2015
DOI: 10.1007/s10096-015-2464-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota modulate the immune effect against hepatitis B virus infection

Abstract: The immunological mechanisms by which hepatitis B virus (HBV) initiates and maintains acute or chronic infection, even the formation of cirrhosis and hepatocellular carcinoma, are still undefined. An increasing number of studies have shown that intestinal flora regulate immune homeostasis, and, thus, protect the immunologic function against hepatitis virus infection. In this article, we discuss gut microbiota and its potential immune effects against HBV infection. It may provide a novel insight into the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 91 publications
(105 reference statements)
0
31
0
1
Order By: Relevance
“…Additionally, micro‐ecological studies have found that the occurrence and development of hepatitis may be closely related to intestinal flora (Xu, Huang, & Wang, ). Moreover, most herbal medicines are administered orally.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, micro‐ecological studies have found that the occurrence and development of hepatitis may be closely related to intestinal flora (Xu, Huang, & Wang, ). Moreover, most herbal medicines are administered orally.…”
Section: Resultsmentioning
confidence: 99%
“…Various immune cells and cytokines not only are involved in the initiation and regulation of the immune response but also can activate downstream signaling pathways that directly or indirectly inhibit HBV replication. It can be concluded that the host immune response caused by HBV infection exerts a significant influence on the prognosis of hepatitis B and the treatment effect of antiviral drugs [ 12 ]. The immune response against HBV mainly includes innate immunity and adaptive immunity; however, the effective innate immune response not only can eliminate the virus directly but also can exert a significant influence on HBV-specific immunity [ 13 ].…”
Section: Chronic Hbv Infection and Innate Immunitymentioning
confidence: 99%
“…After the breach of the body's physical barriers, such as the skin or mucous membranes by microorganisms, TLRs identify molecules and become activated, leading to immune responses [ 14 ]. TLRs are expressed in multiple liver immune cells, including plasmacytoid dendritic cells (pDCs), monocytes, macrophages, Kupffer cells, hepatic stellate cells, and liver cells [ 12 ]. Experimental studies have indicated that the activation of cell signaling pathways by TLRs and the release of antiviral cytokines are the main mechanisms by which HBV replication in liver cells is suppressed.…”
Section: Chronic Hbv Infection and Innate Immunitymentioning
confidence: 99%
“…Так, представители Firmicutes -лакто-бактерии и бифидобактерии -влияют на ин-дукцию IgA, дифференцировку разных типов иммунных клеток (Th1, Th17, Foxp3 + регуля-торные T клетки и др. ), а также участвуют в ре-ализации защиты организма от гепатотропных вирусов [19,36,37,48,62]. В частности, штаммы Lactobacillus casei Shirоta обладают свойством смещать баланс (Th) от Тh2 в сторону Th1, игра-ющих роль в реакциях клеточного иммунитета и обеспечивающих противовирусный имму-нитет.…”
Section: Abstract: Chronic Hepatitis Liver Cirrhosis Immune Systemunclassified